2020
DOI: 10.1097/ccm.0000000000004267
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antibiotic Discontinuation Strategies on Mortality and Infectious Complications in Critically Ill Septic Patients: A Meta-Analysis and Trial Sequential Analysis*

Abstract: Objective: To investigate methods of antibiotic duration minimization and their effect on mortality and infectious complications in critically ill patients. Data Sources: A systematic search of PubMed, Embase (via Ovid), clinicaltrials.gov, and the Cochrane Central Register of Controlled Trials (via Wiley) (CENTRAL, Issue 2, 2015). Study Selection: Randomized clinical trials comparing strategies to minimize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…A duration of ATB therapy of 7–10 days is generally adequate for sepsis patients, and longer courses are necessary only in some patients, such as those with slow clinical response or with undrainable foci [ 18 ]. A shorter duration of ATB therapy even in sepsis patients is safe without affecting treatment success [ 19 ]. Decisions on the duration of ATB should be considered depending on patient-related factors and the type of infection [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…A duration of ATB therapy of 7–10 days is generally adequate for sepsis patients, and longer courses are necessary only in some patients, such as those with slow clinical response or with undrainable foci [ 18 ]. A shorter duration of ATB therapy even in sepsis patients is safe without affecting treatment success [ 19 ]. Decisions on the duration of ATB should be considered depending on patient-related factors and the type of infection [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The undesirable effects of using procalcitonin along with clinical evaluation to decide when to discontinue antimicrobials are considered minimal, and do not outweigh the potential benefits [ 322 ]. Limited data on the cost-effectiveness are available, although a single centre study reported decreased hospital costs associated with PCT-guided antibiotic in medical ICU patient with undifferentiated sepsis [ 323 ].…”
Section: Infectionmentioning
confidence: 99%
“…Neutropenia [204,208] Surrogate markers such as Serum or Bronchoalveolar Lavage Galactomannan Assay [209][210][211] Haematopoietic stem cell transplantation [204,208,212] Solid organ transplantation [202,[212][213][214] High dose corticosteroid therapy [215,216] Certain biologic response modifiers [206,217,218] outweigh the potential benefits [322]. Limited data on the cost-effectiveness are available, although a single centre study reported decreased hospital costs associated with PCT-guided antibiotic in medical ICU patient with undifferentiated sepsis [323].…”
Section: Risk Factor For Invasive Mold Infectionmentioning
confidence: 99%
“…However, procalcitonin is more helpful in identifying Gram-negative bacterial systemic infections [25], and the accuracy of procalcitonin in predicting Gram-negative bacteremia in leukemia patients is quite good (area under the receiver operating characteristic curve (AUROC) = 0.779) [26]. Longitudinal assessment using serial procalcitonin measurements can predict prognosis and treatment efficacy in infections [27], and this assessment is used in antibiotic stewardship [28][29][30]. Procalcitonin is also used as an independent predictor of clinical deterioration in ED patients with suspected sepsis [31].…”
Section: Introductionmentioning
confidence: 99%